‘I will help you/us with Justice’: A Design Process veiled in Secrecy (Bulletin KNOB, 2022)
The Department of Justice on Het Plein in The Hague eventually came into being between 1876 and circa 1885 after a turbulent design history characterized by quarrels, backbiting and posturing.The design has traditionally been attributed to Cornelis Peters, even though its style is not typical for him. It was suspected at the time that the architect Pierre Cuypers and the civil servant Victor de Stuers were involved to some degree. Now new archival research has made it possible to confirm their role and to clear up the uncertainty surrounding the design’s authorship. After an initial design for the new Justice building by J.F. Metzelaar had been rejected, L.H.J.J. Mazel, head engineer in the Waterstaat (civil engineering) department of the Ministry of the Interior, and his deputy, J. Singels, produced a basic concept and ground plans. Hugo Pieter Vogel, an architect of note, was engaged to design the visually defining facades. In April 1876 these plans were considered by a Board of Government Advisers dominated by Cuypers and De Stuers. After lengthy discussions, the advisers rejected Mazel and Singels’ plans. Behind the scenes Cuypers proceeded to sketch new plans, in two versions, which were then elaborated by Mazel and Singels. Vogel, who was supposed to adapt his elevation designs to suit the new ground plans, felt under pressure from De Stuers to work in the traditional Dutch architectural style. As an. architect in the classical tradition, Vogel took exception to this and withdrew acrimoniously. This cleared the way for Cuypers and De Stuers to impose their own elevation designs via Cuypers’ ex-pupil Cornelis Peters, whom they had managed to get appointed as architect in the Department of Finance in early 1876. Peters, who was recruited in October 1876, initially signed his drawings and memos with the pseudonym ‘Nemo’ ('nobody'). As far as the outside world knew, De Stuers and Cuypers were not involved in the design. Once Peters had been officially appointed to oversee the construction of the Justice building in February 1877, he no longer needed to be so reticent, but the other two continued to influence the design from the wings. Thus the Justice building was designed under a cloak of secrecy, an artifice intended to conceal De Stuers’ contribution and, more especially, the far-reaching involvement of Cuypers. The main reason for putting Peters forward as designer lay in the seriously impaired relations following Cuypers’ controversial appointment as architect of the Rijksmuseum in Amsterdam in 1876. Cuypers could ill afford another scandal. Although a few contemporaries expressed their suspicions and displeasure, the three gentlemen’s machinations had the desired effect: a Ministry of Justice in their own preferred ‘national’ style.